The Social Skills Improvement System- Rating Scale Preschool Version Parent Form: Validity and Reliability Study - Cansu Tutkun; Çağlayan Dinçer (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In this study, it was aimed to conduct the validity and reliability study of the Social Skills Improvement System- Rating Scale Preschool Version Parent Form. The sample of the study consisted of mothers (n = 226) and fathers (n = 99) of 325 children aged 3-5 who attended different pre-school education institutions. Content validity, confirmatory factor analysis, test-retest reliability and internal consistency coefficient (Cronbach Alpha) were calculated in the analysis of the data. Five experts were consulted for the content validity and 79 items on the scale were decided by the experts to be used on the scale. As a result of confirmatory factor analysis, it was determined that 79 items and 12 factorial structure of the scale generally complied with the collected data. Internal consistency coefficients of the scale changed between .70 and .83. These results showed that The Social Skills Improvement System- Rating Scale Preschool Version Parent Form was a reliable and valid tool for measuring the social skills of children in Turkey.